Effect of high-energy electrons on the thermal, mechanical and fire safety properties of fire-retarded polypropylene nanocomposites - Xiao, Dan; Gohs, Uwe; Wagenknecht, Udo; Voit, Brigitte; Xiao, Xue Qing; Peng, Xiang Fang; Wang, De Yi (Radiation Physics and Chemistry, 2022)
Fire-retarded nanocomposites (FRNC) based on polypropylene, clay and allylamine polyphosphate (PP-FRNC) was processed firstly. Effect of high-energy electrons on the thermal, mechanical and fire safety performances of PP-FRNC were then investigated systematically. After that the relevant fire safety mechanism of irradiated PP-FRNC was discussed. The thermal and mechanical properties of the irradiated PP-FRNC were increased by (electron beam) EB treatment at suitable dose, whereas these properties reduced by high-energy electrons because of the degradation or chain scission of polymer at higher dose. Moreover, the increase dose of EB treatment could improve the LOI values of PP-FRNC. Furthermore, EB treatment modified PP-FRNC improved better quality char residue, which effectively enhance fire safety of PP-FRNC. Particularly, the results suggest that EB treatment is a sustainable green and efficacious surface modification for heat and smoke suppressions rate of FRNC.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Electron-beam treatment; Flame-retarded nanocomposite; Heat release; Smoke toxicity release